2012
DOI: 10.3892/mco.2012.12
|View full text |Cite
|
Sign up to set email alerts
|

Modified FLOX as first-line chemotherapy for metastatic colorectal cancer patients in the public health system in Brazil: Effectiveness and cost-utility analysis

Abstract: Abstract. Incorporation of new drugs for treatment of metastatic colorectal cancer (mCRC) has led to a clear improvement in overall patient survival, the added cost of treatment, however, is a major concern worldwide. The cost-effectiveness of using a modified FLOX (mFLOX) regimen for treating mCRC patients was delineated. In this study, 82 consecutive mCRC patients were treated with leucovorin (LV) at 20 mg/m 2 in combination with weekly bolus of 5-fluorouracil (5-FU) (500 mg/m 2 ) for 6 consecutive weeks and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 12 publications
0
16
0
3
Order By: Relevance
“…9 Some patients received monotherapy with a fluoropyrimidine; actually, more patients with an ECOG PS of 3/4 were treated with monotherapy compared with those with an ECOG PS of 2 (19.4% vs. 39.6%). However, because randomized trials have demonstrated that starting with either monotherapy or polychemotherapy does not influence the overall survival of mCRC patients with an ECOG PS of 0/1, 18 we do not believe survival differences among the ECOG groups could be explained by the choice of first-line therapy.…”
Section: Discussionmentioning
confidence: 98%
“…9 Some patients received monotherapy with a fluoropyrimidine; actually, more patients with an ECOG PS of 3/4 were treated with monotherapy compared with those with an ECOG PS of 2 (19.4% vs. 39.6%). However, because randomized trials have demonstrated that starting with either monotherapy or polychemotherapy does not influence the overall survival of mCRC patients with an ECOG PS of 0/1, 18 we do not believe survival differences among the ECOG groups could be explained by the choice of first-line therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Of note, in a previous study from our institution, the use of mFLOX instead of FOLFOX as first-line therapy led to a cost decrease of R$13,000 (US$3,218) per patient for a treatment duration of 20 weeks. 17 Addition of irinotecan (FOLFOXIRI) or monoclonal antibodies (cetuximab, panitumumab, or bevacizumab) increases treatment costs. In the future, the availability of monoclonal antibody biosimilars may allow treatment intensification at an affordable cost for limited-resources settings.…”
Section: Discussionmentioning
confidence: 99%
“…This regimen does not require the use of an infusion pump and has a lower cost than the other regimens mentioned earlier. 17 We aimed to evaluate surgical and survival outcomes of patients with B/U liver metastases from CRC treated by using conversion chemotherapy with mFLOX followed by surgical resection.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Destaca-se ainda, o uso de medidas profiláticas e o manejo das reações leves e/ou moderadas como importantes possibilidades a serem adotadas para que se evite desfechos mais graves que comprometam o tratamento. 31 Todas essas estratégias, além de agregarem benefícios clínicos, são capazes de promover economicidade aos serviços e sistemas de saú-de, 32,33,34 devendo ser adequadamente analisadas pelos profissionais de saúde no momento da definição do protocolo que será utilizado.…”
Section: Discussionunclassified